GlyTouCan 1.0 – The international glycan structure repository. Issue Volume 44:Issue D1(2016) (17th October 2015) - Aoki-Kinoshita, Kiyoko; Agravat, Sanjay; Aoki, Nobuyuki P.; Arpinar, Sena; Cummings, Richard D.; Fujita, Akihiro; Fujita, Noriaki; Hart, Gerald M.; Haslam, Stuart M.; Kawasaki, Toshisuke; Matsubara, Masaaki; Moreman, Kelley W.; et al.
Abstract: Glycans are known as the third major class of biopolymers, next to DNA and proteins. They cover the surfaces of many cells, serving as the 'face' of cells, whereby other biomolecules and viruses interact. The structure of glycans, however, differs greatly from DNA and proteins in that they are branched, as opposed to linear sequences of amino acids or nucleotides. Therefore, the storage of glycan information in databases, let alone their curation, has been a difficult problem. This has caused many duplicated efforts when integration is attempted between different databases, making an international repository for glycan structures, where unique accession numbers are assigned to every identified glycan structure, necessary. As such, an international team of developers and glycobiologists have collaborated to develop this repository, called GlyTouCan and is available at http://glytoucan.org/, to provide a centralized resource for depositing glycan structures, compositions and topologies, and to retrieve accession numbers for each of these registered entries. This will thus enable researchers to reference glycan structures simply by accession number, as opposed to by chemical structure, which has been a burden to integrate glycomics databases in the past.